Factors related to seatbelt-wearing among rear-seat passengers in Malaysia. - Law, Teik Hua; K. C. Mani, Kulanthayan; Wong, Shaw Voon; Ng, Choy Peng (2013)
The benefit of wearing a rear seatbelt in reducing the risk of motor vehicle crash-related fatalities and injuries has been well documented in previous studies. Wearing a seatbelt not only reduces the risk of injury to rear-seat passengers, but also reduces the risk of injury to front-seat occupant who could be crushed by unbelted rear-seat passengers in a motor vehicle crash. Despite the benefits of wearing a rear seatbelt, its rate of use in Malaysia is generally low. The objective of this study was to identify factors that are associated with the wearing of a seatbelt among rear-seat passengers in Malaysia. Multinomial logistic regression analysis of the results of a questionnaire survey of 1651 rear-seat passengers revealed that rear-seat passengers who were younger, male, single and less educated and who had a perception of a low level of legislation enforcement, a lower risk-aversion and less driving experience (only for passengers who are also drivers) were less likely to wear a rear seatbelt. There was also a significant positive correlation between driver seatbelt and rear seatbelt-wearing behaviour. This implies that, in regards to seatbelt-wearing behaviour, drivers are more likely to adopt the same seatbelt-wearing behaviour when travelling as rear-seat passengers as they do when driving. These findings are crucial to the development of new interventions to increase the compliance rate of wearing a rear seatbelt.